Social network analysis of international student mobility: uncovering the rise of regional hubs - Kondakci, Yasar; Bedenlier, Svenja; Zawacki-Richter, Olaf (Higher Education, 2018)
Research on the patterns of international student mobility and the dynamics shaping these patterns has been dominated by studies reflecting a Western orientation, discourse, and understanding. Considering political, economic, cultural, historical, and ecological factors, this study argues that international student mobility is not only an issue of the economically developed, politically stable, and academically advanced Western world but also one that involves countries with different economic, political, and academic characteristics. Taking into account various theoretical orientations, this study argues that political, economic, cultural, and historical factors have led to the emergence of non-traditional destinations for international students; these countries are labeled as emergent regional hubs. In order to empirically test this, a social network analysis was conducted on a worldwide dataset representing 229 countries. The findings evidenced the strong position of traditional destinations for international students. However, the results also suggest the rise of several regional hubs, which are undergoing internationalization processes in different forms and with different rationales. The mobility patterns in emerging regional hubs deviate from those in traditional destinations, which fundamentally change the nature of internationalization in this context.
Keywords: International student mobility; Regional hubs; Social network analysis